MAKNA ATRIBUT NATAL BAGI SALES PROMOTION GIRL (SPG) MUSLIM DI KOTA PEKANBARU - Sharah Aidha Matroni; Genny Gustina Sari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The Indonesian Ulama Council (MUI) forbids the use of non-Muslim attributes forMuslim employees, including inviting or ordering the use of non-Muslim attributes is haram. Thefatwa issued by the MUI sparked various speculations, meanings and opinions amongIndonesians. Some big sales promotion girl companies are also tied to a number of conduct code(regulation of appearance) where SPG must follow the rules like wearing christmas attributes.Regulations made by companies usually do not see whether employees are Muslim or non-Muslim. This study aimed to find out how the meaning of christmas attributes for Muslim salespromotion girl in Pekanbaru City and how the meaning of fatwa haram MUI related to the use ofchristmas attribute for Muslim sales promotion girl in the city of Pekanbaru.This research used qualitative research method with phenomenology approach. Researchsubjects consisted of fife sales promotion girl in Pekanbaru selected by using purposivetechnique. This study used interview data collection techniques, observation, and researchdocumentation. To achieve the validity of the data in this study, researchers used the extension ofthe following and triangulation.The results showed that the meaning of the Christmas attribute was divided into two, namely thetrue meaning and meaning of use. The true meaning of the natal attribute is as a symbol ofChristianity, the meaning of culture, and the meaning of colors and cypress trees. Furthermorethe meaning of the use of the natal attribute by spg is a profession demands and as a compulsion.Meaning of fatwa haram MUI related to the meaning of use of attribute natal for spg muslimdivided two that is appraised is right and too excessive. Some SPG feel that the fatwa must beobeyed while some others feel that the fatwa cannot be linked to the world of workKeyword: the meaning, sales promotion girl